Growth performance of critically endangered Hypselobarbus pulchellus in biofloc system: Influence of carbon sources on immune response, enzyme and antioxidant activity - Anantharaja, Kanagaraja; Barlaya, Gangadhar; C. H. Raghavendra; B. S. Anand Kumar; G. M. Siddaiah; Radhakrishnan , Kalidoss; Chadha , N. K.; Krishna , Gopal; Routray , P.; Hemaprasanth, K. P. (Indian Journal of Fisheries, 2024)
We investigated the effect of various carbon sources on the production performance of critically endangered Hypselobarbus pulchellus in biofloc system. The experimental setup comprised four biofloc treatment groups with various carbon sources (jaggery, tapioca, rice and corn flour) and a control group. Healthy early fry (0.0068 g) was randomly stocked at 100 individuals per m3 into 15 circular fibre reinforced plastic (FRP) tanks (1000 l) and raised for 90 days. All the tested carbon sources significantly influenced weight gain, weight gain (%) and specific growth rate (SGR), with the jaggery treatment displaying the best growth performance (p<0.05). Fingerling survival rates varied from 93 to 95.67% (p>0.05). Compared to the control, the biofloc groups had significantly lower concentrations of nitrogen compounds, specifically total ammonia nitrogen, nitrite and nitrate concentrations were significantly lowered (0.29, 0.35 and 1.32 mg l-1, respectively) in jaggery treatment (p<0.05). In addition, the treatment using jaggery had a higher amount of plankton biomass and an abundance of the Bacillariophyceae group (80%). All biofloc groups displayed enhanced immune and antioxidant activity compared to the control. The jaggery treatment had elevated levels of lysozyme activity than other treatments (p<0.05). Furthermore, fingerlings raised in BFT treatments had significantly higher amylase, protease and lipase activity (p<0.05). Overall, this study’s findings suggest that the addition of various carbon sources significantly improves the production performance, with jaggery as the best carbon source for critically endangered H. pulchellus fingerling production in biofloc system to ensure sustainability. Keywords: Antioxidant activity, Fingerling, Heterotrophic bacteria, Jaggery, Specific growth rate, Sustainability